2015
DOI: 10.1007/s11120-015-0120-2
|View full text |Cite
|
Sign up to set email alerts
|

How will climate change influence grapevine cv. Tempranillo photosynthesis under different soil textures?

Abstract: While photosynthetic responses to elevated CO2, elevated temperature, or water availability have previously been reported for grapevine as responses to single stress factors, reports on the combined effect of multiple stress factors are scarce. In the present work, we evaluated effects of simulated climate change [CC; 700 ppm CO2, 28/18 °C, and 33/53% relative humidity (RH), day/night] versus current conditions (375 ppm CO2, 24/14 °C, and 45/65% RH), water availability (well-irrigated vs. water deficit), and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
23
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 73 publications
(82 reference statements)
9
23
0
Order By: Relevance
“…In vines treated with and without water stress and with and without increasing CO2 concentration (700ppm), the plants under stress had lower values for SC, while plants without water stress and without increase in CO2 concentration showed the highest values (LEIBAR et al, 2015). The results were similar to those obtained in the present study.…”
Section: Resultssupporting
confidence: 90%
“…In vines treated with and without water stress and with and without increasing CO2 concentration (700ppm), the plants under stress had lower values for SC, while plants without water stress and without increase in CO2 concentration showed the highest values (LEIBAR et al, 2015). The results were similar to those obtained in the present study.…”
Section: Resultssupporting
confidence: 90%
“…As reported by Leibar et al (2015), at veraison there were no differences in stomatal conductance, but at maturity, water- ). Among well-watered plants, there were no differences between FCC and Curr in leaf transpiration (Leibar et al, 2015). Therefore, the lower Ca and Zn In this regard, Esteban et al (1999) reported that the absorption of K may be limited in dry soils.…”
Section: Karimsupporting
confidence: 70%
“…The effects could be more or less pronounced when grapevines grow under these conditions for several years. As an example it is largely stated that plants acclimated its photosynthesis rate to high CO 2 atmospheric concentration as it was reported at this experiment (Leibar et al, 2015).…”
Section: Karimsupporting
confidence: 60%
See 2 more Smart Citations